KUALITAS AIR IRIGASI PADA KAWASAN INDUSTRI DI KECAMATAN KEBAKKRAMAT KABUPATEN KARANGANYAR - Sari Mukti Rohmawati; Sutarno Sutarno; Mujiyo Mujiyo (Caraka Tani: Journal of Sustainable Agriculture, 2016)
Subdistrict Kebakkaramat was the region with the most extensive area of rice fields and the highest rice production, in addition to the Subdistricts Kebakkramat a number of industrial areas with the greatest number two after Jaten Subdistricts. Industry in the Subdistrict Kebakkramat is dominated by the textile industry and agriculture are mostly located in areas suspected of liquid waste that contaminate irrigation water for paddy soil. Pollution caused by industrial waste, will reduce the quality of irrigation water. The purpose of this study was to determine the quality of irrigation water in the industrial area Subdistricts Kebakkaramat. This research used descriptive quantitative method implemented through field surveys and continued by laboratorium analysis. Observation variables of the quality of irrigation water include temperature, TDS, pH, DHL, DO, nitrate and metals Cr. The results showed that the TDS, pH, DHL, DO and nitrate water still in suitable with the irrigation water quality standards according to Government Regulation No. 82 of 2001, while the temperature in point 5 does not correspond to irrigation water quality standard. Cr at all observation points, except the control does not correspond to irrigation water quality standard, that exceeds a predetermined limit is 0.01 ppm.